2010
DOI: 10.1073/pnas.1007071107
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of proton transport through the transmembrane tetrameric M2 protein bundle of the influenza A virus

Abstract: The M2 proton channel from influenza A virus is an essential protein that mediates transport of protons across the viral envelope. This protein has a single transmembrane helix, which tetramerizes into the active channel. At the heart of the conduction mechanism is the exchange of protons between the His37 imidazole moieties of M2 and waters confined to the M2 bundle interior. Protons are conducted as the total charge of the four His37 side chains passes through 2 þ and 3 þ with a pK a near 6. A 1.65 Å resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
520
5
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 248 publications
(574 citation statements)
references
References 54 publications
39
520
5
1
Order By: Relevance
“…Noting that the MD simulations were performed with pH 6.5 crystal structures, it is possible that the fast exchange dynamics observed herein reflect not merely a reorganization of solvent density around differently solvated backbone amides but also reorganization of the water near Ala30 in response to hopping and translocation of a proton between different sites. Considering the strong affinity for water of a protonated histidine, 60 and the proximity of Gly34 to the histidine tetrad, which allows water molecules to bridge between the glycine amide and the imidazole nitrogen, 28 it can be expected that the water near Gly34 is more ordered compared to that near the Ala30 site. This is reflected in the absence of any measurable solvent exchange at the Gly34 site.…”
Section: E Channel Water Dynamics Influences Drug Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Noting that the MD simulations were performed with pH 6.5 crystal structures, it is possible that the fast exchange dynamics observed herein reflect not merely a reorganization of solvent density around differently solvated backbone amides but also reorganization of the water near Ala30 in response to hopping and translocation of a proton between different sites. Considering the strong affinity for water of a protonated histidine, 60 and the proximity of Gly34 to the histidine tetrad, which allows water molecules to bridge between the glycine amide and the imidazole nitrogen, 28 it can be expected that the water near Gly34 is more ordered compared to that near the Ala30 site. This is reflected in the absence of any measurable solvent exchange at the Gly34 site.…”
Section: E Channel Water Dynamics Influences Drug Bindingmentioning
confidence: 99%
“…This tetrad of water molecules has also been observed in X-ray crystallographic measurements. 28 Guided by these previous observations and predictions, a set of ammonium-containing spiro compounds has recently been designed to target the M2 channel with the expectation that drug binding would be significantly stabilized through interactions with the aforementioned carbonyl tetrads and the distinctive water clusters in the channel. 23 While experimental results 23 indeed indicate that this series of spiro compounds has high affinity toward the M2 channel, MD simulations 23 suggest that the spiro compound binds in an amantadine-like mode deeper within the channel, docking itself in the pore through interactions with the water cluster near Gly34 (Figure 1(c)).…”
Section: Introductionmentioning
confidence: 99%
“…However, the water dynamics in the AM2 protein probed using 2D infrared (2D-IR) spectroscopy revealed that the well-ordered "ice-like" pore water dynamics at pH 8.0 change to more mobile and "liquid-like" dynamics (on the timescale of a few picoseconds) at pH 3.2 (23). This result suggests an interesting pH-dependent behavior of the AM2 protein that is highly relevant for understanding its PT mechanism.Although many computational studies have investigated the features of AM2 that may influence its PT in recent years (12,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), only a few have explicitly simulated any aspect of the explicit PT process (24,25,29,37,38). This is because it is challenging to accurately model the charge delocalization and Grotthuss shuttling of the hydrated excess proton in a computationally tractable way.…”
mentioning
confidence: 99%
“…The protein has been the target of antiviral drugs amantadine and rimantadine (4,5). Much effort has been devoted to discovering the structure and proton transport (PT) mechanism of the AM2 channel, resulting in many crystal structures available in the protein data bank (6)(7)(8)(9)(10)(11)(12)(13)(14). Based on the crystal structures and electrophysiology experiments, several PT models have been suggested.…”
mentioning
confidence: 99%
“…These reactions imply a cyclic reaction scheme and are related to the resetting of the protonation-induced tilting of the helices. 33,34 For further details see. 11…”
Section: An Example For the Kinetic Analysis Of Membrane Transportmentioning
confidence: 99%